1979
DOI: 10.1002/art.1780220404
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of prolonged hyperbaric oxygen in adjuvant arthritis of the rat

Abstract: Development of adjuvant disease in the rat is suppressed if hyperbaric oxygen is administered within one day after the inoculation of an oil suspension of Mycobacterium tuberculosis and continued for 16 to 17 days. Although 10 to 40% of the rodents developed mild arthritis after discontinuance of therapy, most remained symptom-free for at least 50 days. Oxygen administered after arthritis is advanced still exerted a significant curative effect. Possible mechanisms underlying the therapeutic action of oxygen ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…One study used HBO at 2.4 ATA and 100% oxygen, which is equivalent to diclofenac 20 mg/kg [35]. HBO has also been shown to decrease the symptoms of advanced arthritis in rats [36], and it attenuated the inflammatory response in the peritoneal cavity caused by injected meconium [37]. In addition, one study using HBO at 2.5 ATA showed increased survival and decreased proteinuria, anti-dsDNA antibody titers, and immune-complex deposition in lupusprone autoimmune mice [38].…”
Section: Discussionmentioning
confidence: 97%
“…One study used HBO at 2.4 ATA and 100% oxygen, which is equivalent to diclofenac 20 mg/kg [35]. HBO has also been shown to decrease the symptoms of advanced arthritis in rats [36], and it attenuated the inflammatory response in the peritoneal cavity caused by injected meconium [37]. In addition, one study using HBO at 2.5 ATA showed increased survival and decreased proteinuria, anti-dsDNA antibody titers, and immune-complex deposition in lupusprone autoimmune mice [38].…”
Section: Discussionmentioning
confidence: 97%
“…HBOT has also been shown to decrease the symptoms of advanced arthritis in rats [96] and attenuates the inflammatory response in the peritoneal cavity caused by injected meconium [97]. In addition, one animal study using HBOT at 2.5 ATA showed increased survival and decreased proteinuria, anti-dsDNA antibody titers, and immune-complex deposition in lupus-prone autoimmune mice [98].…”
Section: Hbot Use In Inflammatory Conditionsmentioning
confidence: 99%
“…Experimentally, HBO 2 treatment can reduce allodynia in rats with peripheral nerve injuries (Thompson et al, 2010; Li et al, 2011; Gu et al, 2012; Zhang et al, 2012) and experimental arthritis (Warren et al, 1979; Wilson et al, 2006, 2007). Research from our laboratory demonstrated that HBO 2 treatment effectively reduces pain in animal models of acute pain (Ohgami et al, 2009; Zelinski et al, 2009a; Chung et al, 2010; Quock et al, 2011).…”
Section: Introductionmentioning
confidence: 99%